Canadian University Students’ Experiences of Addiction Recovery: A Pilot Study - Burns, Victoria F.; Ethier, Ashley; Hadad, Noor; Hennessy, Emily; Szeto, Andrew (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2025)
Addiction is a critical concern on Canadian post-secondary campuses, yet recovery remains largely overlooked. Guided by a recovery capital framework, this pilot survey explored the recovery characteristics, supports, and barriers among 101 Canadian university students (average age 24.5). Participants reflected diversity across gender (men 49.5%, women 39.6%, minoritized 10.9%), sexual orientation (LGBTQIA2S+ 46.5%), and race/ethnicity (racially minoritized 45.5%). Recovery pathways were primarily abstinence-based (59.4%), followed by non-abstinence approaches (25.7%) and those unsure (9.9%). Students reported recovering from alcohol (44.6%), cannabis (26.7%), self-harm (24.8%), nicotine (23.8%), and eating issues (21.8%). The most useful supports were individual therapy (52.5%), media (35.6%), and peer groups (33.7%). Barriers included fear of losing coping mechanisms (63.4%) and minimizing problem severity (48.5%). Most students viewed campus as recovery-threatening (68.3%) and called for more supports, particularly substance-free residence housing (74.3%) and better access to services (29.7%). Findings underscore the need for recovery-inclusive strategies in Canadian higher education.